Cardiometabolic risk in children and adolescents: mediation analysis of crosssectional study. [Riesgo cardiometabólico en niños y adolescentes: análisis de mediación de un estudio transversal]. - Noelia González-Gálvez; Jose Carlos Ribeiro; Jorge Mota (Ramón Cantó Alcaraz, 2021)
The aims of this study were a) to assess whether obesity acts as a mediator between i) cardiorespiratory fitness (CRF) and mean blood pressure; and ii) between between physical activity (PA) and mean blodd pressure in children and adolescents. A cross-sectional study was conducted with a 632 children and adolescents. It was measured mean blood pressure, body mass index, fat mass and waist circumference. CRF and PA was assessing with Course Navette test and ActiGraph. The analysis of the mediation was performed using Process macro for SPSS. The results indicate that obesity acts as a partial mediation in the association between CRF and mean blood pressure in 10-12 years old children (z=from -5.81 to -5.40; all p˂0.000). These results indicate that obesity acts as a complete mediator in the association between PA and mean blood pressure in 10-12 years old children (z=from -4.49 to -1.94; all p˂0.000). Our result reinforces the relevance of prevent weight increse and improve cardiorespiratory fitness level since erly age in children and adolescents to prevent high mean blood pressure. Increasing the level of physical activity can influence on obesity and cardiorespiratory fitness.